Contextualization of Utilities in Law and Maqasid Al-Shariah in Halal Lifestyle Culture in Makassar City - Fikri Fikri; Aris Aris; Agus Muchsin; Amira Ezzat Mahrous (IAIN Manado, 2023)
This study aims to explain the contextualization of utility in law and maqasid al-shariah towards the halal lifestyle in Makassar City. The study is field research using a normative juridical approach. Data collection procedures were conducted by observing several malls, drug stores, markets, and restaurants, in-depth interviews with Islamic jurists, and documentation. Data analysis by strengthening the utility theory proposed by Jeremy Bentham and maqasid al-shariah put forward by Abu Ishaq al-Syatibi. The study's findings are that the cultural transformation of the halal lifestyle is a form of commitment by the Muslim community in Makassar City to obeying and implementing Islamic law. The contextualization of utility in law and maqasid al-shariah towards the halal lifestyle is to maintain and safeguard religion, human intellect, and soul (nafs). Following up on the findings in this study, a halal lifestyle culture in Makassar recommends further research to optimize living laws in society and the legal system in laws and regulations.